Solar Energetic Particles A Modern Primer on Understanding Sources, Acceleration and Propagation - Reames, Donald V. (Lecture Notes in Physics,, 2021)
This open access book serves as a concise primer introducing the non-specialist reader to the physics of solar energetic particles (SEP). It systematically reviews the evidence for the two main mechanisms which lead to the so-called impulsive and gradual SEP events. This second edition contains two completely new chapters discussing element abundances and shock waves, reflecting new theoretical, modeling, and observational results. Existing chapters have been substantially expanded or updated with additions placed in a broader context. More specifically, the author discusses the timing of the onsets of SEPs, their longitude distributions, their high-energy spectral shapes, their correlations with other solar phenomena, as well as the all-important elemental and isotopic abundances. The book relates impulsive SEP events to magnetic reconnection in solar flares and jets. The concept of shock acceleration by scattering on self-amplified Alfvén waves is introduced, as is the evidence of reacceleration of impulsive-SEP material in the seed population accessed by the shocks in gradual events. The text then develops processes of transport of ions out to an observer. Finally, a technique to determine the source plasma temperature in both impulsive and gradual events is demonstrated.The author also mentions the role of SEP events as a radiation hazard in space and briefly discusses the nature of the main particle telescope designs that have contributed to most of the SEP measurements.